2017
DOI: 10.1007/s00431-017-2946-4
|View full text |Cite
|
Sign up to set email alerts
|

Rural versus urban compliance in the management of cryptorchidism: is there a difference?

Abstract: In this study, a pattern of delayed referral and intervention was observed at both institutions despite differing geographic regions and heterogeneous patient populations. It is important that referring providers realize that scrotal U/S does not change management of UDT and should not delay prompt referral. What is known: • Significant referral delay is a challenging issue in the management of cryptorchidism. • Ultrasound is not a valid method for the detection of cryptorchidism. What is new: • The rural and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…In the Chinese study, the authors observed that in their survey of 305 primary health-care practitioners, only 64% would perform normal pediatric urology examination and only 26% would refer the patient to pediatric surgery prior to 1 year of age 11 . In the US study, the delays in referral and treatment were similar in the urban and rural populations, suggesting that this issue is pervasive in both studied populations 12 . Common reasons for the delayed referral from primary care providers include the following: not understanding the time frame to refer a patient with UDT to attain the benefit of surgical treatment; not performing follow-up genital exams during subsequent care visits; the misperception that it takes time (that is, more than 1 year) for the testicles to descend; the misinterpretation of the guidelines in believing that one has to wait until age 5 or later to refer; the misunderstanding that hormone therapy is first-line treatment instead of surgical intervention; and the misperception that scrotal ultrasound is a valid method for the detection of cryptorchidism that must be routinely performed prior to referral.…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…In the Chinese study, the authors observed that in their survey of 305 primary health-care practitioners, only 64% would perform normal pediatric urology examination and only 26% would refer the patient to pediatric surgery prior to 1 year of age 11 . In the US study, the delays in referral and treatment were similar in the urban and rural populations, suggesting that this issue is pervasive in both studied populations 12 . Common reasons for the delayed referral from primary care providers include the following: not understanding the time frame to refer a patient with UDT to attain the benefit of surgical treatment; not performing follow-up genital exams during subsequent care visits; the misperception that it takes time (that is, more than 1 year) for the testicles to descend; the misinterpretation of the guidelines in believing that one has to wait until age 5 or later to refer; the misunderstanding that hormone therapy is first-line treatment instead of surgical intervention; and the misperception that scrotal ultrasound is a valid method for the detection of cryptorchidism that must be routinely performed prior to referral.…”
mentioning
confidence: 64%
“…However, the target of recommended age of orchidopexy (prior to 1 year of age) was not achieved in any of the years that were studied. Correspondingly, in a 2017 study conducted in collaboration between West Virginia University and Johns Hopkins University, the authors evaluated 131 cases of UDT at an urban center and 100 at a rural center in the US 12 . The average ages of referral were 48.3 months at the urban center and 59.6 months at the rural center; the average ages of surgical intervention were 53.8 and 65.2 months, respectively.…”
mentioning
confidence: 99%
“…10 Despite this early evidence, subsequent studies have demonstrated that the referral and treatment pattern for UDT is less than optimal with large percentages of patients undergoing surgical correction outside of the guideline recommended timeframe. 8 , 9 , 11 …”
Section: Discussionmentioning
confidence: 99%
“…A follow-up study comparing rural and urban referral patterns was conducted and among the two distinct populations there was no significant difference found in time of surgery, time of referral, time between referral and surgery, or patients who underwent evaluation with scrotal US prior to referral. 9 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation